Improvement of developmental competence of cloned male pig embryos by short hairpin ribonucleic acid (shRNA) vector-based but not small interfering RNA (siRNA)-mediated RNA interference (RNAi) of Xist expression - Xuqiong YANG; Xiao WU; Yang YANG; Ting GU; Linjun HONG; Enqin ZHENG; Zheng XU; Fang ZENG; Junsong SHI; Rong ZHOU; Gengyuan CAI; Zhenfang WU; et al. (The Society for Reproduction and Development, 2019)
Xist is an X-linked ribonucleic acid (RNA) gene responsible for the cis induction of X chromosome inactivation (XCI). In cloned mammalian embryos, Xist is ectopically activated at the morula to blastocyst stage on the X chromosome that is supposed to be active, thus resulting in abnormal XCI. Suppression of erroneous Xist expression by injecting small interfering RNA (siRNA) remarkably increased the developmental efficiency of cloned male mouse embryos by approximately 10-fold. However, injection of anti-Xist siRNA resulted in only a slight increase in the developmental ability of injected cloned male pig embryos because the blocking effect of the injected siRNA was not maintained beyond the morula stage, which is 5 days post-activation. To develop a more effective approach for suppressing the ectopic expression of Xist in cloned pig embryos, we compared the silencing effect of short hairpin RNA (shRNA) and siRNA on Xist expression and the effects of these two Xist knockdown methods on the developmental competence of cloned male pig embryos. Results indicated that an shRNA-based RNA interference (RNAi) has a longer blocking effect on Xist expression than an siRNA-mediated RNAi. Injection of anti-Xist shRNA plasmid into two-cell-stage cloned male pig embryos effectively suppressed Xist expression, rescued XCI at the blastocyst stage, and improved the in vitro developmental ability of injected cloned embryos. These positive effects, however, were not observed in cloned male pig embryos injected with anti-Xist siRNA. This study demonstrates that vector-based rather than siRNA-mediated RNAi of Xist expression can be employed to improve pig cloning efficiency.